Decontamination effects of low-temperature plasma generated by corona discharge. Part II: new insights - Scholtz, V; Julák, J; Kríha, V; Mosinger, J; Kopecká, S (Prague medical report, 2007)
The second part of our paper presents the results of experiments with the decontamination of surfaces by low-temperature plasma generated by corona discharge in air at atmospheric pressure. A simple device is described and the effects of the corona discharge on model microorganisms, viz. the yeast Candida albicans, Gram-negative bacteria Escherichia coli, Enterobacter aerogenes, Neisseria sicca, Stenotrophomonas maltophilia, Gram-positive bacteria Deinococcus radiodurans, Enterococcus faecium, Staphylococcus epidermidis, Streptococcus sanguinis, and vegetative and spore forms of Geobacillus stearothermophilus are discussed. A similar microbicidal effect after about one-minute exposure was observed in all vegetative forms of the microorganisms. Measurement in growth inhibition zones on a semisolid medium was used to determine the dependence of the microbicidal effect on exposure time and the distance between electrodes. Counting of colonies served to assess the microbicidal effect of the discharge on contaminated inert surfaces observable after more than 1 min exposure. Geobacillus stearothermophilus spores were found to have several times lower susceptibility to the action of the discharge and the microbicidal effect was observed only after an 8 min exposure. Reaction with the iodide reagent did not unambiguously demonstrate the difference between ozone and singlet oxygen as presumed active components of the corona. The area distribution of reactive oxygen species was determined; it was found to differ from the Wartburg law depending on exposure time. Qualitative evidence was obtained on the penetration of the reactive oxygen species into the semisolid medium.
Keywords: Bacteria; elektřina; Electricity; Candida; dekontaminace; Decontamination